Fracture recurrence in hip fracture with menopausal hormone therapy versus risedronate: a clinical trial. (4th July 2021) - Park, C.-W.; Lim, S.-J.; Moon, Y.-W.; Choi, S.-H.; Shin, M.-H.; Min, Y.-K.; Yoon, B.-K.; Park, Y.-S.
Abstract: Objectives: An open-label, randomized trial was conducted to examine the effects of risedronate versus menopausal hormone therapy (MHT) in postmenopausal women with recent hip fracture. Methods: Among 1165 eligible women, 281 were recruited and randomly assigned to receive oral risedronate (35 mg/week) or percutaneous estradiol gel (1.5 mg/day) plus oral micronized progesterone (100 mg/day) for 4 years. The primary end point was recurrent fracture and the secondary end points were mortality and bone mineral density (BMD). Results: Kaplan–Meier analyses showed no significant differences in fracture recurrence and mortality between the two groups. The incidence of any new fracture per 100 person-years (PY) was 8.63 in the risedronate group and 12.86 in the MHT group ( p  = 0.180); that of clinical fracture was 4.75 and 6.99, respectively ( p  = 0.265); and that of asymptomatic vertebral fracture was 4.87 and 5.58, respectively ( p  = 0.764). The respective incidence of death per 100 PY was 3.58 and 4.40 ( p  = 0.503). BMD increased comparably at the lumbar spine in both groups. BMD at the total hip did not change in the risedronate group, but increased significantly by 2.8% in the MHT group. Conclusions: MHT might not differ from risedronate in the prevention of secondary fractures and death among postmenopausal women with recent hip fracture.